Hydrogen production from water splitting using TiO2 /CoS composite photocatalyst - Mutia Agustina,; Moridon, Siti Nurul Falaein; Amilia Linggawati,; Khuzaimah Arifin,; Lorna Jeffery Minggu,; Mohammad Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Photocatalytic water splitting reaction has been considered an ideal method for hydrogen generation. In this study, a composite of TiO2 /CoS photocatalyst prepared by hydrothermal synthesis method assisted by ball milling crushing process was used. The TiO2 /CoS composites prepared with three variation compositions of 90/10, 80/20, and 70/30 were named M-10, M-20, and M-30, respectively. Field-emission scanning electron microscopy images showed that the morphologies of the composites were porous and uniform of nanospheres. The X-ray diffraction and energy dispersive spectroscopy analyses confirmed the presence of CoS in the composites. Ultraviolet–visible absorption characterization demonstrated the smallest bandgap value of approximately 2.72 eV presented by sample M-30 with the photocurrent density of 0.32 mA cm−2 at 0.9 V vs. Ag/AgCl. The presence of CoS in this study could increase the PC hydrogen generation of TiO2 by nearly 2.5 times. The composites forming a p-n heterojunction between TiO2 and CoS could prevent electron–hole recombination and increase the overall photoactivity of TiO2. .